ANALYSIS OF LEGAL ASPECTS OF STORAGE OF MEDICAL PRODUCTS APPOINTED FOR MEDICAL AND SANITARY CONSEQUENCES OF EMERGENCIES MITIGATION - G. Ya. Ibragimova; R. V. Nasyrov; A. Kh. Gaisarov (Фармация и фармакология (Пятигорск), 2015)
The article analyzes principal legal aspects of medical products storage, appointed for medical and sanitary consequences of emergencies mitigation. We have revealed that nowadays there is a whole range of legal gaps and uncertainties in the regulation of medical products storage. We have also offered the ways for their solution